Language attitudes and beliefs of University EFL teachers and students towards the use of the English language as a Medium of Instruction (MOI): A case study of Mandalay University’s implementation of the 2016 National Language Policy - Win, Khin Su Su (Animo Repository, 2022)
This paper examines Myanmar's national language policy and its influence on EMI implementation in EFL classes. This paper argues that NLP, which aims to transform education by focusing on the full development of students by teaching quality and solid foundations, does not force students to use English widely as an intermediary in the teaching of EFL classes in Myanmar. This paper also addresses the attitudes and beliefs of teachers and students regarding EMI. Language attitudes and beliefs are often seen as the first step in the implementation of language policy, and the positive attitudes and beliefs of teachers and students in the use of language contribute to the success of language policies. The study used policy documents as key data and interviewed 46 teachers and students for secondary sources. Data were analyzed using the qualitative method with an interpretative design based on content analysis. The findings suggested that national language policy reflects the different perspectives and aspirations of education reform among stakeholders seeking to implement EMI policy. Although there has been a positive response from teachers and students to EMI policy, the official language allows teachers and students to be dissatisfied with their language choices. It reflects the views of most stakeholders who still face major challenges in English language outcomes. The findings also showed that teachers and students who face many challenges in teaching EMI believe that EMI policy is an integral part of improving education. A good reason for this is that there are high expectations for higher education in Myanmar.